The essential first year - Leach, Penelope (New York, N.Y DK Publishing, 2010)
New guide to pregnancy and parenting from Penelope Leach, including guidance on practical issues such as feeding, sleeping, and crying
Pregnancy and birth -- New baby, new parents -- Settling in and moving forward -- A member of the family -- Not exactly a baby, nor quite a child
Includes bibliographical references (p. 288) and index
1
Keywords: Child rearing; Infants -- Care